Trajectories of functioning in bipolar disorders: A longitudinal study in the FondaMental Advanced Centers of Expertise in Bipolar Disorders cohort. (October 2020) - Godin, Ophelia; Leboyer, Marion; Mazroui, Yassin; Aouizerate, Bruno; Azorin, Jean-Michel; Raoul, Belzeaux; Bellivier, Frank; Polosan, Mircea; Courtet, Philippe; Dubertret, Caroline; Henry, Chantal; Kahn, Jean-Pierre; et al.
Objective: We aimed at identifying distinct trajectories of functioning and at describing their respective clinical characteristics in a cohort of individuals with bipolar disorders. Methods: We included a sample of 2351 individuals with bipolar disorders who have been followed-up to 3 years as part as the FondaMental Advanced Centers of Expertise in Bipolar Disorders cohort. Global functioning was measured using the Functioning Assessment Short Test. We used latent class mixed models to identify distinct longitudinal trajectories of functioning over 3 years. Multivariable logistic regression models were used to identify the baseline factors that were associated with the membership to each trajectory of functioning. Results: Three distinct trajectories of functioning were identified: (1) a majority of individuals (72%) had a stable trajectory of mild functional impairment, (2) 20% of individuals had a stable trajectory of severe functional impairment and (3) 8% of individuals had a trajectory of moderate functional impairment that improved over time. The membership to a trajectory of stable severe versus stable mild functional impairment was associated with unemployment, a higher number of previous hospitalizations, childhood maltreatment, a higher level of residual depressive symptoms, higher sleep disturbances, a higher body mass index and a higher number of psychotropic medications being prescribed at baseline. The model that included these seven factors led to an area under the curve of 0.85. Conclusion: This study enabled to stratify individuals with bipolar disorders according to three distinct trajectories of functioning. The results regarding the potential determinants of the trajectory of severe functional impairment needs to be replicated in independent samples. Nevertheless, these potential determinants may represent possible therapeutic targets to improve the prognosis of those patients at risk of persistent poor functioning.